How Can the Organizing Work Involved in the Joint Regulation of Lean Projects Promote an Enabling Organization and Occupational Health? - Bruère, Sébastien; Bellemare, Marie; Caroly, Sandrine (Relations industrielles / Industrial Relations, 2018)
The objective of this article is, through an empirical study, to further understanding of the actions and decisions taken in the context of Lean implementation projects carried out under joint regulation (Lévesque and Murray, 1998) agreements. We, therefore, attempt to identify factors that may facilitate the organizing work involved in joint regulation of Lean projects to allow workers to develop a broader range of health-minded work methods and habits.Our assumption is that factors which influence joint regulation, such as the union’s capacity for action, management’s attitude and the purpose of the change, also influence the occupational health outcomes of Lean projects. We believe that the organizing work involved in joint regulation (actions and decisions) has an impact on these factors and influences the occupational health outcomes. Our research question is therefore this: What are the actions and decisions involved in joint regulation of Lean implementation projects that lead to closer correspondence with enabling organization criteria?This empirical study was exploratory in nature and had a multiple case study design. Two cases of lean projects were documented through eight individual interviews and the collection of documents.The main results indicate that, while joint regulation appears essential in terms of meeting enabling organization criteria, it alone is insufficient to explain the health effects of Lean projects. All stakeholders need to define the project goals, modes of assessment and management rules, both cooperatively and transparently, and through their involvement in decisions regarding all processes.